Enhancement of tribological properties of metal phosphate composite coatings with the addition of tin - Kong, H.; Han, H. -G. (ELSEVIER SCIENCE SA, 2015)
The tribological performance of metal phosphate composite coatings for sliding parts at 400 degrees C was experimentally evaluated. In this work, an aluminum-magnesium-chromium phosphate composite binder was fabricated and the binder was mixed with WS2, MoS2, graphite, and Sb2O3 as lubricating fillers. The friction coefficients and wear lives of the coated specimens of various formulations in sliding contact against S45C disc at 400 degrees C in air were tested and compared using a reciprocating friction test rig. Results showed that the average friction coefficients of composite coatings were improved by about 40% when Sb2O3 is replaced by Sn in the same amount of material formulation. It was observed that the addition of Sn resulted in a lower friction coefficient presumably by the melt lubrication effect. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: ALUMINUM PHOSPHATE; MAGNESIA; SILVER